Cognitive Stimulation Induces Differential Gene Expression in Octopus vulgaris: The Key Role of Protocadherins - Valeria Maselli; Gianluca Polese; Al-Sayed Al-Soudy; Maria Buglione; Anna Di Cosmo (Biology, 2020)
Octopuses are unique invertebrates, with sophisticated and flexible behaviors controlled by a high degree of brain plasticity, learning, and memory. Moreover, in Octopus vulgaris, it has been demonstrated that animals housed in an enriched environment show adult neurogenesis in specific brain areas. Firstly, we evaluated the optimal acclimatization period needed for an O. vulgaris before starting a cognitive stimulation experiment. Subsequently, we analyzed differential gene expression in specific brain areas in adult animals kept in tested (enriched environment), wild (naturally enriched environment), and control conditions (unenriched environment). We selected and sequenced three protocadherin genes (PCDHs) involved in the development and maintenance of the nervous system; three Pax genes that control cell specification and tissue differentiation; the Elav gene, an earliest marker for neural cells; and the Zic1 gene, involved in early neural formation in the brain. In this paper, we evaluated gene expression levels in O. vulgaris under different cognitive stimulations. Our data shows that Oct-PCDHs genes are upregulated in the learning and lower motor centers in the brain of both tested and wild animals (higher in the latter). Combining these results with our previous studies on O. vulgaris neurogenesis, we proposed that PCDH genes may be involved in adult neurogenesis processes, and related with their cognitive abilities.